Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karywan pada PT. Gusti Sakti Mandiri - Muhammad Tegar Bagas Kesowo; Muhammad Yusuf (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the issue of fluctuating employee performance at PT. Gusti Sakti Mandiri, a company operating in the Maintenance, Repair, and Overhaul (MRO) aircraft industry, where high accuracy, discipline, and teamwork are essential. The main objective of this research is to examine and analyze the effect of leadership style and organizational culture on employee performance. A quantitative associative approach was employed, using primary data collected through structured questionnaires distributed to all 50 permanent employees, applying a saturated sampling technique. The data were analyzed using multiple linear regression supported by statistical testing, including partial tests (t-test), simultaneous tests (F-test), and coefficient of determination. The results indicate that leadership style has a positive but statistically insignificant effect on employee performance. In contrast, organizational culture shows a positive and significant effect on employee performance. Simultaneously, leadership style and organizational culture have a significant combined influence on employee performance. These findings highlight that a strong organizational culture plays a more dominant role in enhancing employee performance, while leadership style functions as a supporting factor. The study provides practical implications for management in strengthening organizational culture as a strategic effort to improve sustainable employee performance.